PENGENALAN WAJAH BERBASIS ESP32-CAM UNTUK SISTEM KUNCI SEPEDA MOTOR - Audianto Putra Malangi Susilo; Denny Darlis; Dwi Andi Nurmantris (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2021)
In recent years, cases of motor vehicle theft that occurred in Indonesia, especially in metropolitan cities, are indicated by a high crime rate. Various efforts have been made to suppress this curanmor number for example by using a keyless system on motors used in high-end motors. The need for this system is increasing along with the vigilance of motorcycle owners for the safety of their personal vehicles. Facial recognition-based motor keys using the ESP32-CAM module are designed as an alternative to the safety system on motorcycles equipped with relays as switches to disconnect and connect the motorcycle's electricity. The working system designed on this tool uses facial recognition technology that can distinguish the face of the owner of the motorcycle from the one that is not so that the listed and recognized face will connect and disconnect the electrical current of the motorcycle so that the motorcycle can be started and vice versa. From the implementation and testing process with 40 trials, the tool can distinguish the face of the owner of the motor with the face that is not the owner of the motor as much as 80% for the correct condition and 17.5% for the wrong condition.